Ampliación del área de distribución geográfica de oxybelis fulgidus (serpentes: colubridae) y agkistrodon bilineatus (serpentes: viperidae) en la planicie costera central de Oaxaca, México - García-Grajales, Jesús; Buenrostro-Silva, Alejandra (Instituto de Ecología, A.C., 2011)
This report indicates the presence of Oxybelis fulgidus and Agkistrodon bilineatus in Parque Nacional Lagunas de Chacahua, Oaxaca, extending their distribution from its known range to 286 and 343 km NW respectively.